Evaluation of harvested mushrooms and viability of Agaricus bisporus growth using casing materials made from spent mushroom substrate - Pardo-Gimenez, Arturo; Pardo-Gonzalez, Jose E.; Zied, Diego C. [UNESP] (Wiley-Blackwell, 2011)
P>The present work evaluates of harvested mushroom and viability of Agaricus bisporus growth in several casing materials based on spent mushroom substrate. The experiment consisted of eight casing layer, which six were made with spent mushroom substrate. The results confirm the usefulness of reincorporating the spent substrate in new cultivation cycles as an ingredient of casing mixtures. In general, biological efficiency was high, three of the SMS based-casings surpassing the threshold value of 100 kg 100 kg-1 of compost. The high electrical conductivity of mixtures containing a large proportion of spent substrate limits the extent to which it can be used, although mixing it with other materials (such as peat) reduces these values to acceptable levels. In short, it makes economic and environmental sense to reuse spent mushroom substrate as an ingredient of alternative casing materials.
Keywords: Agaricus bisporus; biological efficiency; mushroom quality; spent mushroom compost